Perspectives on research directions in cement and concrete - Provis, John L. (Journal of Asian Concrete Federation, 2025)
This paper marks the 20th anniversary of the Asian Concrete Federation by taking a perspective-style overview of current research directions in cementitious materials, and the concretes made from them. Despite a (sometimes well-earned) reputation for conservatism, the cement and concrete sector is a hotbed of innovation and creativity, and there are many opportunities to better leverage these innovative and creative processes through collaborations between specialists in fields including (but not limited to) chemical, materials, process, concrete technology, structural engineering, and engineering design. Many routes are currently being investigated for “green cement” or “green concrete” production, and it is important to carefully consider and assess which of these are likely to give the most feasible (and most rapid), pathways to deep carbon emissions reductions. To achieve sustainability, we need to make better cements, to make better concretes, and to use these concretes better in practical engineering applications. This paper provides some thoughts about how this may be able to be achieved, with the intention of sparking future discussions and developments.